The impact of financial risks on the profitability of commercial banks: An analytical study of Al Waha Main Bank (Comprehensive Journal of Science, 2026)
This study aimed to analyze the impact of financial risks on the profitability of Libyan commercial banks through an applied study on Al-Waha Commercial Bank, which served as the sample for the research during the period from 2013 to 2020. The study focused on three types of financial risks: liquidity risk, credit risk, and capital adequacy risk. Profitability was measured using two main indicators: Return on Assets (ROA) and Return on Equity (ROE). The study adopted the descriptive analytical approach and employed the multiple linear regression model to analyze the relationship between the independent variables (financial risks) and the dependent variables (profitability), using the statistical software E-Views 12. The study reached the following conclusions: there is no significant impact of financial risks (liquidity, credit, capital adequacy) on the profitability of Al-Waha Commercial Bank, and no statistical significance was found between each type of financial risk and the profitability indicators (ROA, ROE). In light of these findings, the study recommends strengthening the efficiency of financial risk management in Libyan commercial banks, improving financial analysis and evaluation mechanisms, and developing internal policies that help address potential risks, thereby contributing to financial stability and achieving sustainable profitability.